Prostate cancer screening with PSA: new data, old debate - Stefania Sciallero; Giuseppe Fornarini (Frontiers Media S.A., 2011)
Two prostate cancer screening randomised controlled trials from Europe (European Randomised Study of Screening for Prostate Cancer-ERSPC) and U.S. (Prostate, Lung, Colorectal, and Ovarian Cancer Screening Program- PLCO) have been published earlier this year...